Digital Technology-Based Approaches To Improving Energy Efficiency In Industrial Enterprises - Majidov Omadbek (Euro Asian Journal Publishing, 2025)
Improving energy efficiency in industrial enterprises has become a strategic priority in achieving sustainable development and reducing operational costs. With the advent of Industry 4.0, digital technologies such as the Internet of Things (IoT), artificial intelligence (AI), big data analytics, and smart sensors offer new opportunities for optimizing energy consumption. This paper explores various digital approaches to enhancing energy efficiency, focusing on their implementation in industrial settings. It discusses the integration of energy management systems (EMS), real-time monitoring platforms, predictive maintenance tools, and intelligent automation. The research presents case studies and quantitative assessments demonstrating the potential energy savings and economic benefits of digital interventions. Furthermore, it addresses the barriers to digital adoption, including technical, organizational, and financial challenges, and proposes a framework for successfully transitioning towards smart, energy-efficient industrial operations. The findings suggest that systematic adoption of digital solutions can lead to a 15–30% reduction in energy consumption, improved process transparency, and long-term competitiveness for industrial enterprises
Keywords: Energy Efficiency; Industrial Enterprises; Digital Technologies